2019
DOI: 10.31699/ijcpe.2019.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methyl Orange from Wastewater by using Biochar

Abstract: The biochar prepared from sawdust raw material was applied in this study for the treatment of wastewater polluted with methyl orange dye. The effect of pH (2-11), initial concertation (50-250 mg/L) and time were studied. The isotherm of Langmuir, Frendluch and temkin models studied. The Langmuir model was the best to explain the adsorption process, maximum uptake was 136.67 mg/g at 25Co of methyl orange dye. Equilibrium reached after four hours of contact for most adsorbents.The values of thermodynamic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…They can remain in the environment for a long period of time if they are not addressed with an adequate treatment [3,4].…”
Section: -Introductionmentioning
confidence: 99%
“…They can remain in the environment for a long period of time if they are not addressed with an adequate treatment [3,4].…”
Section: -Introductionmentioning
confidence: 99%
“…The previously reported research with biomass‐derived biochar for the adsorption of MO was very efficient. Some of the reported adsorbents for MO adsorption are pulp sludge (Chaukura et al, 2017), chicken manure (Yu et al, 2018), sawdust biochar (Abdulrahman Hanoon & Ahmed, 2019), pomelo peel waste (Zhang et al, 2020), with maximum adsorption capacities of 16.05, 39.47, 136.67, and 163.105 mg/g, respectively. In this study, the synthesized activated biochar at 500°C showed the efficiency of 99.3% removal and 175 mg/g capacity, which is superior than many graphitic sorbents (Chowdhury et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19]. Previous studies showed that AC can be prepared from agro wastes such as date stones [15,18,[20][21][22], coconut shell [15], scrape tires [18], chitin [23], sawdust [24], seaweed [25]. In terms of OS, previous researchers mostly focused on its carbonization and a composite of sewage sludge along with the production of porous carbon using it with physical or chemical activation [26].…”
Section: Introductionmentioning
confidence: 99%